A process for the identification and analysis of scientific articles in conference proceedings - Silva Coimbra, Fernanda; Rodrigues Dias, Thiago Magela (Advanced Notes in Information Science, 2022)
Scientific events fulfil several functions in the context of science. It is an excellent means of communication between scientists, giving internal and external visibility to the works presented. Scientific production has been growing significantly, and, consequently, understanding the behavior of this trend has become essential. The results presented at events, usually published in proceedings, aim to show what was broadcast and debated during the event. Given the above, this study seeks to give characteristics of Brazilian scientific production published in event proceedings, using the curricula registered in the Lattes Platform as a data source. From our analysis, we identified and discussed the large areas that have more excellent representation in the analyzed set; a temporal analysis is allowed us to verify the years with the most significant number of publications. It was possible to confirm if any persistent identifier was used in the records of these publications.